Epizootic situation for infectious bovine rhinotracheitis in the Karaganda Oblast, the Republic of Kazakhstan, in 2021–2022 - V. V. Kirpichenko; F. A. Bakieva; S. B. Mamanova; E. K. Ospanov; S. E. Kaimoldina (Ветеринария сегодня)
A comprehensive serological monitoring is currently underway in the Republic of Kazakhstan to detect the circulation of the infectious bovine rhinotracheitis pathogen. To conduct a full-fledged and resultful study, the principles of sampling size representativeness provision and mathematical calculations were observed.The sampling size of the total number of epizootological units included mainly the raions and settlements in which (or near which) infectious bovine rhinotracheitis cases had been previously recorded. The sampling size of livestock population included in the study was determined in accordance with the recommendations of the World Organization for Animal Health. Thus, the study covered 7 (out of 13) raions of the Karaganda Oblast in 2021 and 2022. The other 6 raions and cities of regional significance will be included in the research in 2023. The paper presents the results of infectious bovine rhinotracheitis retrospective analysis and own studies conducted in 2021–2022. Statistical analysis and graphical visualization of investigation results were performed using Statistica, Excel, and QGIS programs.It was established that the epizootic situation for this disease was unfavourable in the Karaganda Oblast in 2021–2022. The data and results of serological studies presented by the Veterinary Control and Surveillance Committee of the Ministry of Agriculture of the Republic of Kazakhstan confirm the circulation of the infectious bovine rhinotracheitis virus in the following raions of the Karaganda Oblast: Abay, Aktogay, Bukhar-Zhyrau, Karkaraly, Nura and Osakarov.